2015
DOI: 10.1021/acs.bioconjchem.5b00183
|View full text |Cite
|
Sign up to set email alerts
|

Nanotechnological Approaches to Therapeutic Delivery Using Elastin-Like Recombinamers

Abstract: This review discusses the use of elastin-like polymers and their recombinant version, elastinlike recombinamers, in drug-delivery systems. These macromolecules exhibit a number of interesting properties that are rarely found together in any other family of materials, especially extremely high biocompatibility, high bioactivity and functionality, complex yet fully controlled composition and stimuli responsiveness.Appropriate design of these molecules opens up a broad range of different possibilities for their u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 113 publications
0
17
0
Order By: Relevance
“…In addition, tumor-specific promoters provide a safe and effective strategy for designing gene-therapy systems that can be adapted for use with various tumors or delivery systems. To date, ELRs and other polymers widely used as non-viral vectors, such as poly-lysine (PLL), polyethylenimine (PEI), polyethyleneglycol (PEG), chitosan, poly(lactic-co-glycolic acid) (PLGA), or poly(2-dimethylaminoethyl methacrylate) (pDMAEMA) [20], have found increasing applications in biomedicine due their inherent biocompatibility and smart properties [21][22][23][24][25][26][27][28][29]. A previous study showed the ability of ELRs joined to functional peptides to be used as delivery vectors with no cellular effects in vitro [30].…”
Section: Breast Cancer Is the Most Commonly Occurring Cancer Diagnosementioning
confidence: 99%
“…In addition, tumor-specific promoters provide a safe and effective strategy for designing gene-therapy systems that can be adapted for use with various tumors or delivery systems. To date, ELRs and other polymers widely used as non-viral vectors, such as poly-lysine (PLL), polyethylenimine (PEI), polyethyleneglycol (PEG), chitosan, poly(lactic-co-glycolic acid) (PLGA), or poly(2-dimethylaminoethyl methacrylate) (pDMAEMA) [20], have found increasing applications in biomedicine due their inherent biocompatibility and smart properties [21][22][23][24][25][26][27][28][29]. A previous study showed the ability of ELRs joined to functional peptides to be used as delivery vectors with no cellular effects in vitro [30].…”
Section: Breast Cancer Is the Most Commonly Occurring Cancer Diagnosementioning
confidence: 99%
“…Furthermore, we will comment the diverse applications inferred from the control of their ordered-disordered state. Moreover, while several publications have already reviewed the use of ELRs in drug delivery [20,21] and in tissue engineering and regenerative medicine (TERM) [1,[22][23][24], herein we will point out the major advances in the multi-purpose design and use of ELRs in these fields in the past few years. Finally, we will describe other designs and applications that do not completely fit into the aforementioned sections.…”
Section: Introductionmentioning
confidence: 99%
“…In tissue engineering, hydrogels have been the predominant matrices for application in the human body in the last 40 years (165,(188)(189)(190). ELRs are non-immunogenic, and according with their biodegradability and biocompatibility for human tissue, blood, and other fluids, they can play a key role as carriers in delivery systems (189,191,192).…”
Section: Elr-based Hydrogelsmentioning
confidence: 99%
“…Furgerson's group to deliver an EGFP−plasmid inside cells in in vitro assays (193). The use of specifically designed ELRs joined to functional peptides as agents shows promising results for delivering genes in vitro (190). Moreover, cellular transfection can be improved through the formation of charged polyplexes and their further interaction with the negatively charged components on the cell membrane, such as proteoglycans and cell-surface receptors (194,195).…”
Section: Elrs Have Been Previously Used As Oligo-lysine Carriers Bymentioning
confidence: 99%
See 1 more Smart Citation